PERBANDINGAN METODE PEMBELAJARAN BLENDED LEARNING MENGGUNAKAN POWERPOINT DIPANDU ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR FISIKA SISWA DI SMP NEGERI 7 PALU DAN SMP NEGERI 9 PALU - Saadjad, Danti Y. (JSTT, 2016)
This study aims to determine the physics students' learning outcome in SMP Negeri 7 Palu and SMP Negeri 9 Palu applied learning method using blended learning. The study design used is quasy design experiment. Data were analyzed using t-test. Samples were class VII A in SMP Negeri 7 Palu applied learning methods blended learning using face to face and media guided powerpoint animation and class VII G at SMP Negeri 9 Palu as a comparison experiment with applied learning methods blended learning using face to face and models powerpoint, which is determined by cluster sampling technique. The results showed that the application of blended learning teaching methods to the learning outcomes of students in the physics of motion in SMP 7 Palu and SMP 9 Palu (thit (= 0,39) < ttable (= 2,01)). Thus, it can be concluded that the application of learning methods blended learning using face to face and media guided powerpoint animation in SMP Negeri 7 Palu on learning outcomes of students' physics can be increased and the results studied physics at SMP Negeri 7 Palu and SMP 9 Palu was not significantly different means there is no difference in the results of studying physics.